TALENT AND PROJECT CLASSES DALAM PENGUATAN ENTREPRENEURIAL SKILLS PADA KOMUNITAS BERLIAN DI PKBM KAK SETO TANGERANG SELATAN - Tyan, M. Mas’addien Dwi; Hilmi, Muhammad Irfan; Purnamawati, Frimha (IKIP Siliwangi, 2025)
Marginalized groups are identified as low-income communities facing functional limitations, particularly in creating sustainable practical entrepreneurship. The Berlian Community at PKBM Kak Seto plays an active role in developing entrepreneurial skills among marginalized children as a form of social intervention in South Tangerang. This study aims to describe talent and project classes in strengthening entrepreneurial skills within the Berlian Community at PKBM Kak Seto, South Tangerang. This research employs a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. The data analysis techniques consist of data collection, data reduction, data presentation, and verification or conclusion drawing. Data validity techniques include prolonged participation, persistent observation, and triangulation. The research findings reveal three key phases: in the choosing project topic stage, participants are able to design food product strategies and understand entrepreneurial values; in the designing project plan stage, they develop a strong foundation for building an effective entrepreneurial mindset; and in the finishing the project stage, participants demonstrate adaptability to future market dynamics. In conclusion, project-based learning has successfully facilitated participants’ gradual self-improvement, although more intensive guidance is required to maximize the reinforcement of their entrepreneurial skills